2001
DOI: 10.1094/cchem.2001.78.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gliadin Fractions on Functional Properties of Wheat Dough Depending on Molecular Size and Hydrophobicity

Abstract: The effects of α‐ + β‐, γ‐, ω‐ and total gliadins on mixing, extension baking, and techno‐functional properties of doughs from hard and soft flours were measured using small‐scale techniques. The addition of all gliadin fractions resulted in decreased mixing time, peak resistance, maximum resistance to extension, and loaf height, and in increased resistance breakdown and extensibility. The various gliadin fractions showed differences in functional properties, with γ‐gliadin reducing the mixing time and maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 15 publications
6
52
0
2
Order By: Relevance
“…28,41 Some of the differences observed in dough properties between cultivars may be due to differences in LMW-GS and gliadin composition. 7,31 However, these alone do not account for variability in dough properties. Recent reports 42,43 indicate that the glutenin-to-gliadin ratio also plays a role in determining dough properties.…”
Section: Flour Protein Composition and Flour Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…28,41 Some of the differences observed in dough properties between cultivars may be due to differences in LMW-GS and gliadin composition. 7,31 However, these alone do not account for variability in dough properties. Recent reports 42,43 indicate that the glutenin-to-gliadin ratio also plays a role in determining dough properties.…”
Section: Flour Protein Composition and Flour Qualitymentioning
confidence: 99%
“…Wheat protein quality depends on the presence or absence of specific high-molecular-weight glutenin subunits (HMW-GS), 4 low-molecular-weight glutenin subunits (LMW-GS) 5 and gliadins. 6,7 It also depends on the ratio of monomeric to polymeric proteins 8,9 and the molecular size distribution of glutenin. 10 The importance of accurate assessment of protein composition as a tool in understanding the biochemical basis of wheat quality has long been recognised.…”
Section: Introductionmentioning
confidence: 99%
“…10) makes a significantly larger contribution to dough properties than those encoded by Glu-B1 (17 ? 18), while subunit 1 encoded by Glu-A1 made the smallest contribution to functionality [39]. Sontag-Strohm et al found that progeny carrying allele Glu-A1b (subunit 2*) had significantly greater SDS sedimentation-volumes than the null allele Glu-A1c, and that adding a HMW glutenin subunit affected extensiograph dough strength more than adding a LMW glutenin subunit, although both increased the SDSsedimentation volumes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Fido et al (1997) isolated and purified individual groups of gliadins (α-, beta-, γ-, ω-1 and ω-2) and observed all to be reducing the dough strength on addition to flour. Uthayakumaran et al, (2001) also observed that the added gliadin fractions decreased the mixing time, peak resistance, maximum resistance to extension, and loaf height, and increased resistance breakdown and extensibility. The rheological tests are the most commonly used test to determine the quality of the flour.…”
Section: 8) Wheat Dough Qualitymentioning
confidence: 71%
“…In chapatti, gliadins are found to increase the extensibility of dough (Paterson and Piggott, 2006). Khatkar et al, (2002) found gliadins to positively affect the bread loaf volume, while Uthayakumaran et al, (2001) found contradictory results. Prabhasankar (2002) proposed that chapatti making quality is relative to lower levels of gliadin content, whereas (Ram and Nigam, 1982) proposed quantity of glutenin, gliadins and residual proteins as responsible for good chapatti quality.…”
Section: 11) Molecular Basis Of Wheat Quality and Wheat Geneticsmentioning
confidence: 99%